Faktor Yang Memengaruhi Pencegahan Penyakit Dbddi Wilayah Kerja Puskesmas Aekkota Batu Kabupaten Labuhanbatu Utara - Zulham Aliwardana Ritonga; Tri Niswati Utami; Asriwati Asriwati (Jurnal Ventilator, 2024)
Dengue Fever (DBD) is an infectious disease caused by dengue virus of the genus Flavivirus, family Flaviviridae which can be transmitted through the bite of Aedesaegypti mosquitoes infected with dengue virus to humans. The purpose of the study was to determine the factors that influence the prevention of dengue fever in the Working Area of Puskesmas Aekkota Batu, North Labuhanbatu Regency. The research design used quantitative methods carried out analytical surveys with a Cross Sectional Study approach. The population in this study were all people in the Aekkota Batu Health Center Working Area consisting of 9 villages, namely 19,271 family heads. The sample used a Stratified Random Sampling system of 99 family heads. Data analysis used univariate, bivariate and multivariate analysis with logistic regressionThe results showed that there was an influence of knowledge, attitudes, the role of health workers, water reservoirs and the presence of garbage on the prevention of dengue fever in the Working Area of Puskesmas Aekkota Batu, North Labuhanbatu Regency. While the most dominant factor is knowledge p = 0.000 < 0.025 and 95% CI = 7,270-385,013 with OR = 52,907. This means that knowledge has 52 times the risk compared to other variables.The conclusion of this study is that knowledge, attitudes, the role of health workers, water reservoirs and the presence of garbage affect the prevention of dengue fever in the Aekkota Batu Health Center Working Area, North Labuhanbatu Regency. It is recommended to the Puskesmas Aekkota Batu to conduct routine flick checks every 3 months, carry out fogging and increase health promotion to the community on how to prevent DBD by implementing 3M plus in order to reduce the incidence of DBD.